The Association between Physical Activity and Cognitive Function: Data from the China Health and Nutrition Survey. (20th June 2022) - Huang, Qiankun; Zhao, Jing; Jiang, Weiqing; Wang, Wenfeng
Abstract : Background . Decreased cognitive function is a common problem in the old adults, which has high risk of progression to Alzheimer's diseases (AD) and other dementias. This study was aimed at finding out the association between physical activity and cognitive function. Methods. In total, 1514 participants with the age ≥ 55 years old registered in the China Health and Nutrition Survey (CHNS) database were selected in this study. The association between physical activity and cognitive function was analyzed via the generalized additive model. The association between the variables and the cognitive function score was expressed as β coefficient with 95% confidence intervals (CIs). Results . After adjusting age, ethnicity, stratum, marital status, education, memory status, and memory changes, the cognitive function score was increased by 0.011 points for every 1-point increase in domestic score (β = 0.011, P = 0.043 ). Subgroup analysis indicated that in the female group, for every 1-point increase in the domestic score, the cognitive function score increased by 0.019 points (β = 0.019, P = 0.017 ). In people with good memory status, each 1-point increase in domestic score increased the cognitive function score of 0.020 points (β = 0.020, P = 0.017 ). Conclusions . The decreased cognitive function was correlated with decreased domestic physical activity. The increased domestic physical activity was associated with an increased cognitive function in females and people with good memory status. The findings might offer a reference for deep understanding of the association between physical activity and cognitive function.